In Search of a Preventive Approach to Management of the Meliaceas Borer (Hypsipyla grandella) - Hilje, Luko (2020)
This paper summarizes the author and collaborators’ research experiences in the search for preventative methods to deal with Hypsipyla grandella (Lepidoptera: Pyralidae). Based upon the paradigm of integrated pest management (IPM), they include graftings of Cedrela odorata on a resistant rootstock of Australian cedar (Toona ciliata var. australis), the structuration of ecologically-robust plantations, based on plant diversification and natural biological control, the design of a risk prediction system, early population abatement through pheromone-baited traps,  avoidance by adult repellence or larval deterrence, and larval mortality due to toxicity or growth disruption.